Designing and implementing a training program on surgical hand scrubbing, wearing surgical cap and surgical mask, gowning, and gloving using HMD-based virtual reality technologies for nursing students: an exploration of student perceptions - Güngör, Songül; Yava, Ayla; Koyuncu, Aynur (Frontiers in Medicine, 2024)
The aim of this study is to determine the steps of a training program utilizing Head-Mounted Display (HMD) based Virtual Reality Technology to enhance nursing students' skills in surgical hand scrubbing, wearing surgical cap and surgical mask, gowning and gloving, and to evaluate students' perceptions towards the program. Methods: The study aimed to investigate the potential applications of HMD-Based Virtual Reality Technology in Surgical Hand Scrubbing, Wearing Surgical Cap and Surgical Mask, Gowning and Gloving Program for nursing students, as well as students' perceptions towards this technology. The research was conducted with a focus group consisting of second -year nursing students in Osmaniye/Turkey, between January and June 2022, and the training program was implemented in five stages: Analysis, Design, Development, Implementation, and Evaluation. The program was evaluated with a focus group of nursing students. Focus group discussions were conducted to provide insights into students' experiences, feedback, and perceptions of the program.Results: A vast majority of participants (92.5%) reported feeling fully immersed in the operating room environment during the virtual reality (VR) experience. Notably, all students acknowledged the potential of HMD-Based Virtual Reality Technology to enrich their understanding of surgical hand scrubbing, wearing surgical cap and surgical mask, gowning and gloving procedures, surpassing conventional instructional models. While many participants found the experience exhilarating (85.1%), a considerable portion reported a decline in engagement after repeated exposures (88.8%). Overall, participants welcomed the integration of VR technology into education, expressing optimism about its capacity to facilitate additional instructional modules (74.4%). Moreover, they conveyed satisfaction with the opportunity to engage with the VR application, emphasizing its significant educational value (81.4%).Based on these findings, we can suggest that virtual reality technology has the potential to have an impact on nursing students' education. The majority of students expressing a sense of presence in the operating room highlights the value of this method in education. However, the reported boredom after repeated experiences by most participants underscores the importance of diversifying the program and introducing innovative approaches to keep students engaged.